Lifestyle changes during the first and second waves of the COVID-19 pandemic in medical college students: are there gender-related differences? - Coppi, Francesca; Nasi, Milena; Sabatini, Silvia; Bellini, Pierantonio; Generali, Luigi; Mecugni, Daniela; Farinetti, Alberto; Consolo, Ugo; Mattioli, Anna Vittoria (Acta Biomedica Atenei Parmensis, 2022)
Background and aims. The COVID-19 pandemic has seriously affected young people. The present study aims to explore the effects of COVID-19 on lifestyle in 500 undergraduate students both during the acute phase of the pandemic (so-called "first wave") and during the second spread of infections (so-called "second wave"). Gender differences were also explored. Methods and results. During the first wave we found weight gain in 48.6% of subjects, a switch to an unhealthy diet (43%), and an increase in the amount of food introduced (35%). Interestingly, women showed higher intake of food in order to cope, while men privileged higher wine consumption as a coping mechanism. We observed a sharp reduction in physical activity, increased sedentary behaviours and deterioration in sleep quality. Stress correlates with eating to cope (r=0.86; p<0.001); drinking to cope (r=0.83; p<0.001). Contrary to expectations, the second wave led to a situation similar to the first. We have detected a further deterioration in quality of sleep (67% vs 77%; p<0.01) and also a reduction in sleeping time (68.6% vs 77.7; p<0.01). Conclusions. The long pandemic has led to unhealthy lifestyle changes in the student population of our municipality in Northern Italy. There are gender differences in lifestyle modifications developed during the pandemic that suggest a different response to stress. Moreover, the persistence of pandemic-related stress due to the “second wave” has severely affected the lifestyle habits of undergraduate student.